Crop Growth Monitoring Through integration of WSN and IoT - Haoran yu (Computational Algorithms and Numerical Dimensions)
The emerging and revolutionary technology called Internet of Things (IoT), presenting the future of computing, communication, and network, has made a number of tough jobs easier with the help of Internet, sensor, and embedded systems. Agriculture is said to be the backbone of Indian Economy and is of utmost importance in the present scenario. Today’s agriculture is data-centered, precise, and smarter than ever. The research paper explores the various issue and challenges which are vital in the field of smart agriculture using IoT devices. The paper also highlights the importance and usefulness of wireless network and other related terminology in this area. The paper explores the various advances in the field of smart agriculture, IoT, and wireless network and draws attention to the various future research directions that the research community can take to further improve the system in terms of economics, operations, and technical feasibility.